Targeting the Gut Microbiota to Treat Cachexia - Genton, Laurence; Mareschal, Julie; Charretier, Yannick; Lazarevic, Vladimir; Bindels, Laure B.; Schrenzel, Jacques (Frontiers in Cellular and Infection Microbiology, 2019)
Cachexia occurs in many chronic diseases and is associated with increased morbidity and mortality. It is treated by nutritional support but often with limited effectiveness, leading to the search of other therapeutic strategies. The modulation of gut microbiota, whether through pro-, pre-, syn- or antibiotics or fecal transplantation, is attracting ever-growing interest in the field of obesity, but could also be an interesting and innovative alternative for treating cachexia. This article reviews the evidence linking the features of malnutrition, as defined by the Global Leadership Initiative on Malnutrition (low body mass index, unintentional body weight loss, low muscle mass, low appetite and systemic inflammation) and the gut microbiota in human adults with cachexia-associated diseases, and shows the limitations of the present research in that field with suggestions for future directions.